From Page to Stage: Tanika Gupta’s Theatre Adaptation of Jackie Kay’s Memoir Red Dust Road - Giovanna Buonanno (Le Simplegadi)
The stage adaptation of Jackie Kay’s 2010 memoir Red Dust Road written by playwright Tanika Gupta premiered at the Edinburgh International Festival in 2019. The play dramatises Kay’s identity quest as a mixed-race child, born to a Scottish woman from the Highlands and a Nigerian student, and adopted as a baby by a Glaswegian couple in the early 1960s. The article will focus on the strategies Gupta deploys in her rewriting and argue that by incorporating passages from Kay’s poetic oeuvre, Gupta pays a moving tribute to Kay, one of the most powerful voices in black British women’s writing.